(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Abstract. Objective. The aim of this study is to synthesize and investigate the physicochemical and biological properties of complex compounds of 3d metals with imidazole (L1) and 1,2,4-triazole (L2). Methods. The synthesized compounds were characterized by a set of physicochemical methods, including elemental analysis (CHN), thermogravimetric analysis (TGA), X-ray structural analysis (XRD), and infrared spectroscopy (IR). Results. Complexes of various compositions were synthesized by solution reactions between chlorides, sulfates, and nitrates of 3d metals with ligands L1 and L2. IR spectroscopy showed that L1 coordinates through the nitrogen atom N(3) of the imidazole ring as a monodentate ligand. The coordination mode of L2 depends on the composition: in complexes with a 1:4:2 ratio, it acts as a monodentate ligand, whereas in 1:2:2 complexes it behaves as a bidentate bridging ligand, forming polymeric chains. Thermal decomposition of all complexes proceeds in both endothermic and exothermic stages without melting, accompanied by the cleavage of azole rings. X-ray diffraction analysis revealed that the complex CuL1₄Cl₂ (I) crystallizes in a monoclinic system (space group P2₁/n), where the Cu(II) atom forms a tetragonal pyramidal coordination polyhedron. The polymeric isostructural complexes [CoL1₆](NO₃)₂ (II) and [CdL1₆](NO₃)₂ (III) crystallize in a triclinic system (R-3), featuring slightly distorted octahedral coordination. In [ZnL1₂(NO₃)₂(H₂O)₂] (IV), ligand L1 acts as a chelating-bridging ligand, forming zigzag polymeric chains. Biological screening revealed three Cu(II) complexes — CuL1₄Cl₂ (I), CuSO₄·6L1₄·(H₂O)₆ (II), and CuL2₄SO₄·2(H₂O) (III) — exhibiting high cestocidal activity (85–100%) against Echinococcus granulosus protoscoleces and low toxicity (LD₅₀ = 1040–2110 mg/kg).